Visual art history and the psychology of perception: Perspectivism and its 20th century abandonment in the visual arts and in Gibson's ecological psychology. Issue 1 (14th July 2021) - Heft, Harry
Abstract: The development of linear perspective in the early 15th century and the discovery of the retinal image two centuries later became cornerstones of an approach to visual perception theory that eventually took shape primarily in the hands of British Empiricist philosophers. Even as this approach has dominated perceptual theory to the present day, the perspectivist influence on pictorial representation within the visual arts steadily diminished over time. Its decisive break with perspectivism came in the early 20th century with transformative 19th century changes in the sciences and technology. Collectively, these events elevated process and change over fixity and stasis, and ultimately led to the collapse of the distinction between space and time in the physical sciences. Even so, approaches to visual perception in psychology remained remarkably untouched by these occurrences until the 1960s when the experimental psychologist James Gibson drew upon them to challenge the legacy of perspectivism and the visual image and their effect on perceptual theory. His ecological approach to perception recognizes animacy as the essential functional property of living things, and in doing so, conceptualizes seeing as a perception–action process. From this stance, Gibson like the visual artists earlier in the century rejected the assumption that visual perception is best characterized as the capturing of static images. Jointly and yet independently, both efforts loosened the grip that perspectivism and the visual image have maintained on the arts and on visual perception theory, respectively, bringing 19th century scientific advances into 20th century psychological thought.